2008
DOI: 10.1128/iai.01381-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an HLA-A*0201-Restricted T-Cell Epitope on the MPT51 Protein, a Major Secreted Protein Derived fromMycobacterium tuberculosis, by MPT51 Overlapping Peptide Screening

Abstract: CD8؉ T cells play a pivotal role in protection against Mycobacterium tuberculosis infection. We identified a novel HLA-A*0201-restricted CD8؉ T-cell epitope on a dominant secreted antigen of M. tuberculosis, MPT51, in HLA-A*0201 transgenic HHD mice. HHD mice were immunized with plasmid DNA encoding MPT51 with gene gun bombardment, and gamma interferon (IFN-␥) production by the immune splenocytes was analyzed. In response to overlapping synthetic peptides covering the mature MPT51 sequence, the splenocytes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Firstly, we synthesized 10 MPT63-derived peptides which are potentially restricted by HLA-A Ã 0201 and measured their binding affinity for HLA-A Ã 0201 molecules on the basis of T2 cell line. In vivo immunization experiments revealed that among five high-affinity peptides, two (MPT63 [18][19][20][21][22][23][24][25][26] and MPT6 ) triggered cytotoxic T-cell response whereas the remaining three high-affinity peptides failed to induce IFN-g-secreting T-cell responses. Conversely, three low-affinity peptides (MPT63 [10][11][12][13][14][15][16][17][18][19] , MPT63 [20][21][22][23][24][25][26][27][28] and MPT63 [29][30][31][32][33][34][35][36][37] ) all exhibited immunogenicity in HLA-A Ã 0201 transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, we synthesized 10 MPT63-derived peptides which are potentially restricted by HLA-A Ã 0201 and measured their binding affinity for HLA-A Ã 0201 molecules on the basis of T2 cell line. In vivo immunization experiments revealed that among five high-affinity peptides, two (MPT63 [18][19][20][21][22][23][24][25][26] and MPT6 ) triggered cytotoxic T-cell response whereas the remaining three high-affinity peptides failed to induce IFN-g-secreting T-cell responses. Conversely, three low-affinity peptides (MPT63 [10][11][12][13][14][15][16][17][18][19] , MPT63 [20][21][22][23][24][25][26][27][28] and MPT63 [29][30][31][32][33][34][35][36][37] ) all exhibited immunogenicity in HLA-A Ã 0201 transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, four identified overlapping epitopes (MPT63 [5][6][7][8][9][10][11][12][13][14] , MPT63 [10][11][12][13][14][15][16][17][18][19] , MPT63 [18][19][20][21][22][23][24][25][26] and MPT63 [20][21][22][23][24][25][26][27][28] ) are located in a signal peptide sequence (residues 1-29) of MPT63 and span a long peptide with 24 amino acids (residues 5-28, TMIKTAVAVVAMAAIATFAAPVAL). In our previous study, we identified four overlapping HLA-A Ã 0201-restricted CD8 + T-cell epitopes in an amino acid sequence of M. tuberculosis-specific antigen PPE68 (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most HLA-A*0201-restricted T-cell epitopes were nonamer peptides (Falk et al, 1991, Parker, 1994, but some epitopes were decamer peptides. We reported an immunodominant HLA-A*0201-restricted T-cell epitope in MPT51 antigen (Aoshi et al, 2008; Tables 1, 2). Main anchor amino acid positions are, position 2 (Leu) and position 9 (Val), which were conserved in MPT51 p53-62 (TLAGKGISVV) ( Table 2).…”
Section: Fig 1 Shematic Diagram For Identification Of T-cell With Dmentioning
confidence: 96%
“…More recently, using HLA-peptide tetramers derived from Mtb peptides predicted to bind to HLA-A*0201, Tang and his colleagues have found a very interesting Mtb epitopes activating polyfunctional CD8+ T cells in human TB (Tang et al, 2011). Moreover, some specific www.intechopen.com peptides to CD8 T Lymphocytes as HLA-B*35-restricted CD8(+) T-cell epitope in Mtb Rv2903c (Klein et al, 2002), HLA-A*0201-restricted T-cell epitope in the MPT51 protein (Aoshi et al, 2008) and HLA-B*35-restricted CD8 T cell epitopes in the antigen 85 (aa 204-212) WPTLIGLAM (Klein et al, 2001), were demonstrated to have a potential positive effect on Mtb -infected macrophages and produce significant level of gamma interferon and tumor necrosis factor alpha.…”
Section: Reverse Immunogenetic and Tb Diagnosis Test Developmentmentioning
confidence: 99%